2017
DOI: 10.1016/j.biortech.2017.07.099
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the surface properties of biochar by thermal treatment

Abstract: In this work, the effect of controlled thermal treatment to tune biochar surface properties such as area/porosity, functionalities and reactivity was investigated. TG-MS, CHN, Raman, IR, BET, Zeta and SEM analyses suggested that thermal treatment led to the decomposition of an organic complex/amorphous phase to produce micropores based on graphene nanostructures and a strong increase on surface area from 3mg for biochar to 30, 408 and 590mg, at 400, 600 and 800°C, respectively. The treatment also led to a grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…Specific surface area increased with increasing pyrolysis temperature, as shown by others (Domingues et al 2017;Luo et al 2015). This is a function of shrinking the solid matrix, causing relatively large pores to become smaller and thus increasing overall SSA (Weber and Quicker 2018;de Mendonça et al 2017). Surface area has been previously correlated with sorption/retention of nutrients and contaminants, while pore volume (which, in general increases with pyrolysis temperature) is assumed to affect water availability and soil aeration (Ajayi and Horn 2016;Qambrani et al 2017).…”
Section: Pyrolysis Temperaturementioning
confidence: 80%
“…Specific surface area increased with increasing pyrolysis temperature, as shown by others (Domingues et al 2017;Luo et al 2015). This is a function of shrinking the solid matrix, causing relatively large pores to become smaller and thus increasing overall SSA (Weber and Quicker 2018;de Mendonça et al 2017). Surface area has been previously correlated with sorption/retention of nutrients and contaminants, while pore volume (which, in general increases with pyrolysis temperature) is assumed to affect water availability and soil aeration (Ajayi and Horn 2016;Qambrani et al 2017).…”
Section: Pyrolysis Temperaturementioning
confidence: 80%
“…The D band originates from sp 3 hybridization, while the G band is characteristic of crystalline graphitic/sp 2 carbon atoms (Hussain et al, 2012 ; Yan et al, 2016 ). The ratio of G band intensity to D band intensity ( I G / I D ) of BC700 was higher than that of BC500 and BC300, which indicated that the ratio of disordered/ordered graphene structures was increased for BC700 (Mendonça et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of D band is a signature of degree of amorphization, since this band is not related to the selection rules of the detectable vibrational modes through Raman scattering, according to structure of the graphite crystalline lattice (Tuinstra & Koenig, 1970). Formation of amorphous structures probably occurs due to decomposition of amorphous organic structures during the pyrolysis process (Mendonça, Cunha, Soares, Tristão, & Lago, 2017).…”
Section: Biochar Characteristicsmentioning
confidence: 99%